A Carvacrol-Rich Essential Oil Extracted From Oregano (Origanum vulgare “Hot & Spicy”) Exerts Potent Antibacterial Effects Against Staphylococcus aureus - Hao, Yuanpeng; Li, Jingyi; Shi, Lei (Frontiers in Microbiology, 2021)
The present study aimed to investigate the antibacterial effect and mechanism of a carvacrol-rich oregano essential oil (OEO) generated from Origanum vulgare “Hot & Spicy” on the inactivation of Staphylococcus aureus. The gas chromatography–mass spectrometry analysis of the OEO allowed the detection of 27 compounds; the preponderant constituent was carvacrol (84.38% of total compounds). The minimal inhibitory concentration (MIC) and minimum bactericidal concentration of the OEO against S. aureus were 0.125 and 0.25 mg/mL, respectively. The growth curve assay indicated that the OEO prolonged the lag phase of S. aureus, and the time-kill curve assay showed the potent bactericidal activity of the OEO. The decrease in cell viability, changes in the integrity of cell membrane, and abnormal cell morphology further reflected the irreversible damage of S. aureus caused by the OEO. In addition, a label-free proteomic analysis was applied to analyze the regulatory networks of S. aureus in response to 1/2 MIC OEO-treatment stress. Of the 56 differentially expressed proteins (DEPs) identified, 26 were significantly upregulated and 30 downregulated. The Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis indicated that the DEPs were mainly involved in pathways of ribosomes; valine, leucine, and isoleucine biosynthesis; and phenylalanine, tyrosine, and tryptophan biosynthesis, which suggested that the growth inhibition of S. aureus might be due to the disordered effect of the OEO on protein synthesis and amino acid metabolism. These findings deepened our understanding regarding S. aureus survival and metabolism responses to the OEO treatment and suggested that the carvacrol-rich OEO could be used in food production environments to effectively control S. aureus.